2018
DOI: 10.1097/sap.0000000000001542
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Breast Reconstruction on Patients With Upper Extremity Lymphedema

Abstract: Background Breast cancer–related lymphedema (BCRL) is a debilitating condition with morbidity, hindered quality of life, and increased health-related costs. Experimental studies support the use of musculocutaneous flaps for managing animal models with lymphedema. Although vascularized lymph node transfer (VLNT) and lymphovenous anastomosis are used to surgically treat patients with lymphedema, it is not known whether musculocutaneous or adipocutaneous flaps (eg, delayed autologous breast reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Nonetheless, it has been demonstrated that a flap introduced into a LYE affected area serves as a trigger to the formation of new lymphatic vessels (68), because providing roots for lymph outflow. Finally, all the studies reviewed by Sotos agree that delayed breast reconstruction does not have a role in worsening BCRL (69).…”
Section: Discussionmentioning
confidence: 87%
“…Nonetheless, it has been demonstrated that a flap introduced into a LYE affected area serves as a trigger to the formation of new lymphatic vessels (68), because providing roots for lymph outflow. Finally, all the studies reviewed by Sotos agree that delayed breast reconstruction does not have a role in worsening BCRL (69).…”
Section: Discussionmentioning
confidence: 87%
“…According to Siotos et al, patients affected with breast-cancer related lymphedema were more likely to experience improvement after autologous breast reconstruction, regardless of whether VLNT was performed simultaneously. That being said, if VLNT was included in the procedure, it was noted a 4-fold increase in the chance of patients reporting a positive outcome (14).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery in lymphoedema treatment has shown promising results using different approaches such as lymphaticovenular bypass, inguinal lymph node transfer, autologous lymph vessel transplantation, lymphatic venous anastomosis and suction-assisted lipectomy, 84–90 and delayed autologous breast reconstruction was found to improve lymphoedema symptoms in a study by Siotos et al . 91 Treatment of subclinical lymphoedema with compression garments has shown to be effective but requires early diagnosis. 92 Further studies are needed to set a new gold standard and personalise lymphoedema treatment, and we expect our study to supply data for this, as treatment of lymphoedema also will be recorded.…”
Section: Discussionmentioning
confidence: 99%